2020
DOI: 10.3389/fphar.2020.01011
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans as Multifunctional Anti-Elastase and Anti-Inflammatory Drugs in Cystic Fibrosis Lung Disease

Abstract: Neutrophil elastase (NE) is a major protease in the airways of patients with cystic fibrosis (CF) that activates airway inflammation by several mechanisms. NE stimulates epithelial toll like receptors (TLR) resulting in cytokine upregulation and release, upregulates MUC5AC, a major airway mucin, degrades both phagocytic receptors and opsonins resulting in both neutrophil and macrophage phagocytic failure, generates oxidative stress via extracellular generation and uptake of heme free iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 109 publications
0
14
0
Order By: Relevance
“…Cystic fibrosis is an inflammatory lung disease linked with high airway levels of neutrophil elastase. Polysulfated GAGs (including polysulfated HA) are currently used for neutrophil elastase inhibition and because of their anti-inflammatory properties [ 65 ]. HA is also used in other airway related diseases: chronic sinusitis, asthma, bronchiectasis, and chronic obstructive pulmonary disease [ 66 ].…”
Section: Applications Of Hyaluronic Acidmentioning
confidence: 99%
“…Cystic fibrosis is an inflammatory lung disease linked with high airway levels of neutrophil elastase. Polysulfated GAGs (including polysulfated HA) are currently used for neutrophil elastase inhibition and because of their anti-inflammatory properties [ 65 ]. HA is also used in other airway related diseases: chronic sinusitis, asthma, bronchiectasis, and chronic obstructive pulmonary disease [ 66 ].…”
Section: Applications Of Hyaluronic Acidmentioning
confidence: 99%
“…Polysulfated glycosaminoglycans (GAGs) are potent anti-elastase drugs with multiple anti-inflammatory properties [143], and the prototypical drug in this class, heparin, has a strong record of safety and efficacy when administered for other lung disease indications such as asthma, acute lung injury, and smoke inhalation in humans [143]. In one doubleblind, placebo-controlled pilot study, inhalation of unfractionated heparin as a therapeutic for COPD resulted in improved lung function, underscoring the significant promise of GAG therapy for chronic lung diseases [144].…”
Section: Ne Inhibitors and Mechanisms Of Actionmentioning
confidence: 99%
“…A 4-week phase II trial with a neutrophil elastase inhibitor (AZD9668) showed clinical improvements in patients with bronchiectasis [104]. Heparin inhibits neutrophilic elastase, cathepsin-G, blocks P-selectin and L-selectin; nebulized heparin treatment improved the outcome for patients with COPD and asthma [105]. Both MPO and elastase are also crucial mediators in NET formation, so these therapies may interfere with neutrophilic inflammation on several levels.…”
Section: Treatment Strategies For Neutrophils In Chronic Rhinosinusitismentioning
confidence: 99%